Atractylenolide-I restore intestinal barrier function by targeting the S100A9/AMPK/mTOR signaling pathway - Chen, Chen; Sun, Bingjie; Chen, Keming; Bao, Han; Tao, Yu; Zhou, Jinyong; Yuan, Xiaomin; He, Linhai; Lu, Zhihua; Chen, Kaidi; Li, Yang; Yu, Chengli; et al. (Frontiers in Pharmacology, 2025)
Impaired intestinal epithelial barrier function is closely associated with the pathogenesis of ulcerative colitis (UC). Atractylenolide-I (AT-I), a major sesquiterpene derived from the herb Atractylodes macrocephala Koidz., has been reported to alleviate DSS-induced colitis in mice. This study aims to investigated the protective effects of AT-1 on intestinal epithelial barrier function and elucidate it’s underlying mechanisms. In vivo, an acute colitis model was established in mice, and transcriptomic analysis to identify differentially expressed genes. In vitro, overexpression plasmids and recombinant protein were used to evaluate their effects on intestinal barrier function, and further analysis of its potential mechanisms.The study found that AT-1 ameliorate DSS-induced acute ulcerative colitis, exhibiting protective effects on the intestinal barrier. Transcriptomic analysis revealed that AT-1 significantly modulated the expression of S100A8 and S100A9. Further investigations indicated that S100A9, rather than S100A8, mediated the expression of tight junction proteins, meanwhile, AT-1 reduces neutrophil activation and subsequent release of S100A9. Mechanistically, recombinant human S100A9 protein was found to induce a decrease in intracellular Ca2+ concentration, while AT-1 regulated the expression of tight junction proteins via modulation of the AMPK/mTOR signaling pathway. AT-1 enhances the recovery of DSS-induced intestinal barrier dysfunction by regulating the recombinant human S100A9 protein-mediated AMPK/mTOR signaling pathway. This study provides new insights into the pathogenesis of ulcerative colitis and suggests potential therapeutic strategies for its treatment.